Laboratory-based Investigation into the Removal Behaviour of Asphalt in Porous Asphalt Mixture on Zinc Ions from Road Runoff - Yao Zhao (Science Faculty of Chiang Mai University, 2019)
This paper was to investigate the removal behaviour of asphalt in pore-space on dissolved zinc from road runoff based on laboratory experiments. Asphalt films were soaked with different initial concentrations of Zn2+ solutions over 720 h. The surface chemical state of asphalt films before and after experiment were examined by X-ray photoelectron spectroscopy(XPS), while solution samples were analysed for Zn2+ concentrations by an inductively coupled plasma atomic emission spectrometer(ICP-AES). Experimental data were further analysed using both kinetics and adsorption isotherms. It confirmed that Zn2+ in solution had been adsorbed to the asphalt film. The initial stage of adsorption matched both the first-order equation and the parabolic diffusion equation; whereas the entire adsorption process was found fit the second-order equation. Moreover, the adsorptive behaviour satisfied the Freundlich model. These provide evidence to support the adsorption ability of asphalt on the pore-walls in porous asphalt with regard to Zn2+ in road runoff.